Compressive behaviour of 3D printed sandwich structures based on corrugated core design. (March 2021) - Haldar, A.K.; Managuli, V.; Munshi, R.; Agarwal, R.S.; Guan, Z.W.
Abstract: This paper presents a study on corrugated design based 3D printed sandwich panels subjected to quasi-static compression. The study focuses on the investigation of unique corrugated triangular and trapezoidal core designs. Effects of core thickness, skins, height of core and the contact area between core and skins on the mechanical properties of the sandwich panels were investigated through a series of experimental tests. Biodegradable poly-lactic acid thermoplastic filaments reinforced with chopped carbon fibers were used to print sandwich panels. The test results have shown that the compressive strength and energy- absorbing capability of the sandwich panels studied increase rapidly with increasing core thickness. Also, an increase in the contact area between the core and skins results in better mechanical properties.